Eye of Nature. - Walter Phillips Gallery, The Banff Centre School of Fine Arts, Banff; Augaitis, Daina; Dickel, Hans; Fones, Robert; Garneau, David; Graham, Rodney; Moppett, Carroll; Pakasaar, Helga; Poitras, Edward; Sherlock, Maureen P.; Teitelbaum, Matthew; Watson, Scott (Banff : Walter Phillips Gallery - The Banff Centre for the Arts Banff, 1991)
Viola, Bill ; Walker, Laurie ; Kubisch, Christina ; Moppett, Carroll ; Spalding, Jeffrey ; Taho, Ritsuko ; Graham, Rodney ; Fones, Robert ; Poitras, Edward ; Thomson, Tom ; Lisner, Arthur ; Housser, Fred ; Harris, Lawren ; Carr, Emily ; Poitras, Edward ; Struth, Thomas ; Minick, Roger ; Heizer, Michael ; Birds, Hachivi Edgar Heap of
Engels
Eye of Nature, based on exhibitions held June 5 - July 10 / August 3 - September 17 / November 12 - December 17, 1989 at the Walter Phillips Gallery, Banff
boek